Education with BBC micro:bit - Voštinár, Patrik; Knežník, Jaroslav (International Journal of Online and Biomedical Engineering (iJOE), 2020)
Teaching Computer Science in all level of education is not easy, because most students are scared of the programming. Therefore, most of the teachers in Slovak schools prefer to teach special software for a spreadsheet editor, presentation programs, etc. This contribution deals with our experience of using an educational board BBC micro:bit in the educational process. We will explain some of our prepared tasks for teaching programming concepts, which we used for teaching with BBC micro:bit in primary, secondary schools, and university. In the article, we will also focus on various types of extensions, which could be used together with micro:bit. We will explain the results of our research and look at whether using BBC micro:bit can increase the student's motivation for learning programming.